Plant-Derived Psychotropic Agents Targeting Neurotransmitter Systems: Pharmacognostic Evidence, Mechanisms, and Clinical Relevance - Nicky Jaiswal; Kabhi Khanna; Shah Samreen; Km Priyanka Singh; Rifat Siraj (International Journal of Brain Sciences, 2026)
Psychiatric health problems are also a large burden on global health and existing psychotropic drugs may be restricted by relative effectiveness, side effects, and inadequate long-term tolerability. Plant- based psychotropic agents have subsequently been the focus of interest in the form of complementary or alternative therapies. This review outlines the pharmacognostic, mechanisms of action and therapeutic importance of plant-based psychotropic agents against central neurotransmitter systems. The traditional medicinal practices give a lot of information on how botanicals can be used to treat mood disorders, mental anxiety, insomnia and intellectual incapacity. Preclinical evidence reveals that phytochemicals including alkaloids, flavonoids, terpenoids and phenolic compounds regulate serotonergic, dopaminergic, GABAergic and glutamatergic systems and also have neuroprotective and anti-inflammatory effects. The new clinical evidence shows some promise in psychiatric conditions of mild to moderate severity with relatively positive safety and tolerability rates. Nevertheless, issues associated with standardization, dose optimization, herb–drug interactions, and translation restrictions remain. Strict research and clinical validation could help to solve these problems and allow incorporating plant-derived psychotropic agents into the realm of the contemporary psychiatry.
Keywords: Medicinal Plants; Neurotransmitter systems; Pharmacognosy; Phytochemicals; Plant- derived psychotropic agents